Improving the Competitiveness of the Leading Universities of the North Caucasus Federal District in Sync with the Objectives of Regional Development - D. V. Petrosyants; V. V. Zubenko; P. S. Seleznev; I. V. Arzhanova (Высшее образование в России)
The purpose of the work is an analysis of the current state of the universities of the North Caucasus Federal District from the point of view of creating competitive regional development centers, bearing in mind the Spatial Development Strategy of Russia.The research methodology is based on empirical research methods (observation, comparison, data collection and study), current and prospective analysis and synthesis of theoretical and practical material, multivariate systems analysis, sociology, statistical analysis, etc.Results. In the course of the study, features of the development of the NCFD universities were revealed, various aspects of their activities were analyzed. Detailed mapping of the development of the NCFD universities has been made on a wide range of parameters and indicators. The authors note the lack of intelligible parameters used in the formation of the target admission levels in the universities of the North Caucasus Federal District, the weak connection of these figures with the real economy. The absence of status universities in the North Caucasus Federal District, in particular a flagship university, contributes to the outflow of talented students to central Russian and foreign universities.Application area. The results of this work can be applied in the activities of the Ministry of Science and Higher Education of the Russian Federation in developing the new university model – “HEIs, providing personnel for basic branches of regional economy” and in planning the target admission levels of universities, setting goals for universities in the region in terms of synchronization their development programs with administrations for the implementation of national projects, programs for the socioeconomic development of the North Caucasus Federal District.Findings. The peculiarities of the socio-political and economic development of the NCFD indicate the difficulties in planning the training of highly skilled specialists for the region. Despite the fact that the “full range” of educational institutions in the North Caucasus Federal District is economically disadvantageous in the short term, the opportunity for young people to receive higher education in their region can be viewed as one of the few really effective channels of self-realization and socialization for a significant part of North Caucasian youth. Insufficient funding, weak involvement of universities in solving the problems of sustainable development of the region do not contribute to the creation and development of universities which can be the real drivers of sustainable and innovative development of the North Caucasus Federal District and competitive scientific and educational centers.